Media Pembelajaran Perilaku Hidup Bersih dan Sehat menggunakan Metode Gamifikasi berbasis Website - Elizabeth Christina; Merlinda Wibowo (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Students have difficulty in understanding the learning of clean and healthy lifestyle behavior (PHBS) using the lecture method because it is considered boring and less interactive. They also hesitate to ask questions when they don't understand the material. This research aims to create Learning Media for clean and healthy lifestyle behavior using a website-based gamification method, in order to increase student learning motivation by providing interactive learning media and evaluating the feasibility and usefulness of learning media. The research used a Research and Development approach with the ADDIE model, and data collection techniques through observation. This research involved 1 media expert, 2 material experts, teachers, and 30 respondents of 4th and 5th grade students at SD Negeri 3 Purwokerto Kulon as research subjects. Usability evaluation is carried out using the SUS (System usability scale) method. The result of this research is PHBS learning media using website-based gamification method, consisting of 10 pages. Based on the Validation Test by media experts getting a final score of 88.88%, material experts getting a final score of 82.77% and usability evaluation of website-based PHBS learning media by 30 respondents, resulting in a final score of 78.41. Based on the results of the validation and evaluation tests that have been carried out, it can be concluded that this learning media is suitable for use and falls into the acceptable category.